Exploring the relationship between unemployment perception and health during COVID-19: a comparative study of rural and urban adults in China - Zheng, Fengtian; Xiong, Huanhuan; Jin, Yanhong; Zhang, Man (Frontiers in Psychology, 2023)
The COVID-19 pandemic has significantly impacted economies and individual health around the globe. This study uses the China Family Panel Data (CFPS) in 2018 (before the pandemic) and 2020 (during the pandemic) to estimate: a) the relationships between the perceived risk of unemployment and individuals' mental health, physical health, and health behaviors; and b) explore the variations of such relationships between rural and urban adults in China. We find that the perceived risk of unemployment was statistically and positively associated with the risk of depression, and such an association was greater for rural adults than urban adults. The rural-urban variations were observed from many perspectives. The perceived risk of unemployment was statistically and negatively associated with life satisfaction, the probability of gaining weight and becoming obese, the probability of having adequate sleep, and computer-based screen time for rural adults; but the corresponding associations were statistically insignificant for urban adults. On the other hand, the perceived risk of unemployment was statistically and negatively associated with self-rated very good-to-excellent health condition and health-compromising behaviors (smoking and drinking) for urban adults; but such associations were statistically insignificant for rural adults. These findings imply that rural and urban adults had different psychological and behavioral responses to the unemployment risk during the COVID-19 pandemic. Public policies aiming to improve health and employment should be designed from different angles targeting urban and rural populations.